ON N-SOFT HYPERGRAPH - Luthfi Hadiyan Fajri; Yanita Yanita; Admi Nazra; Monika Rianti Helmi (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2026)
In this paper we explore the notion of N-soft hypergraphs, which is an hybridization of N-soft set and hypergraph. Next, we define strong N-soft hypergraphs, and induced complete N-soft hypergraphs. We present the definitions of some of their unary operations and examine their properties. Then, we give illustration on how N-soft hypergraph will be applied in portray real-life problem.